The Effect of a Muscular Endurance Training Programme on Delaying the Onset of Muscle Fatigue and Prolonging Effective Performance Time in Long Bouts Among Fencers at the Telecommunications Club - Humam Sady Ibrahim (Jurnal Pendidikan Kepelatihan Olahraga: PEJUANG, 2026)
Fencing is a combat sport that requires a delicate balance between technical skills and physical abilities, as prolonged bouts place significant demands on the musculoskeletal system, leading to premature fatigue and a decline in performance quality. The significance of this research lies in bridging the gap between the demands of actual competition and the level of muscular endurance among players at Al-Ittisalat Club, through the development of a specialised training programme aimed at enhancing muscular endurance to delay the onset of fatigue and prolong effective performance time. The study hypothesised that there would be statistically significant differences between the pre- and post-tests of the experimental group in terms of fatigue onset and performance time, and between the two groups in favour of the experimental group. The study results showed a significant and substantial improvement in the experimental group (37.7–47.9%) compared to a slight, non-significant improvement in the control group, with highly significant post-test differences, confirming the programme’s effectiveness in enhancing endurance and competitive performance.